A primer on natural product-based virtual screening - Koulouridi, Eleni; Valli, Marilia [UNESP]; Ntie-Kang, Fidele; da Silva Bolzani, Vanderlan [UNESP] (De Gruyter, 2020)
Databases play an important role in various computational techniques, including virtual screening (VS) and molecular modeling in general. These collections of molecules can contain a large amount of information, making them suitable for several drug discovery applications. For example, vendor, bioactivity data or target type can be found when searching a database. The introduction of these data resources and their characteristics is used for the design of an experiment. The description of the construction of a database can also be a good advisor for the creation of a new one. There are free available databases and commercial virtual libraries of molecules. Furthermore, a computational chemist can find databases for a general purpose or a specific subset such as natural products (NPs). In this chapter, NP database resources are presented, along with some guidelines when preparing an NP database for drug discovery purposes.
Keywords: Databases; Library design; Natural products; Natural products databases; Virtual screening